Gestión financiera y contable de la asociación de producción agrícola 6 de octubre-Asoproagroc en la provincia de Los Ríos en el periodo 2021 - 2022. - Vera Jacome, Jean Paul (2024)
Financial and accounting management are considered essential tools in any type of organization, because they allow financial managers to properly manage the organization's resources and thus achieve the established objectives. The objective of this research is to evaluate the financial and accounting management of the Agricultural Production Association 6 De Octubre- Asoproagroc of the province of Los Ríos in the period 2021 - 2022. The study had a mixed approach, the scope was descriptive. The types of research used were: documentary and field; while the methods used were: inductive and deductive, which help analyze the topic from the general to the particular and vice versa. The results of the research allowed us to conclude that: The accounting process in the Agricultural Production Association 6 de Octubre-Asoproagroc is carried out in two phases, so it is concluded that it is not carried out with total effectiveness, since the theory investigated establishes that there are three minimum steps or stages that must be carried out. Follow if the intention is to obtain adequate results that reflect the reality of the business for the respective analyses. The main weaknesses in terms of financial management were: lack of professional analysis regarding the association's financial indicators; On the other hand, there are accounting actions that are being ignored and that are necessary, such as the case of provisions at the close of an accounting year.